2009
DOI: 10.1038/sj.bjc.6604884
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of the transcription factors SOX4, CBFB and SMARCC1 correlates with outcome of colorectal cancer

Abstract: The aim of this study was to identify deregulated transcription factors (TFs) in colorectal cancer (CRC) and to evaluate their relation with the recurrence of stage II CRC and overall survival. Microarray-based transcript profiles of 20 normal mucosas and 424 CRC samples were used to identify 51 TFs displaying differential transcript levels between normal mucosa and CRC. For a subset of these we provide in vitro evidence that deregulation of the Wnt signalling pathway can lead to the alterations observed in ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 35 publications
(51 reference statements)
2
74
1
1
Order By: Relevance
“…It is worth noting that inhibiting Csnk1ε down-regulates the activity of the Wnt/β-catenin signaling pathway that is overactivated in a large proportion of patients with CRC (19). Similarly, alteration of the expression of the transcription factor Smarrc1 is linked to deregulation of the Wnt/β-catenin signaling pathway and to disease severity in CRC (18). Herein, an enhanced expression of paracrine factors that alter the Wnt/β-catenin signaling pathway was also observed within tumors of Nlrp6-deficient mice.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that inhibiting Csnk1ε down-regulates the activity of the Wnt/β-catenin signaling pathway that is overactivated in a large proportion of patients with CRC (19). Similarly, alteration of the expression of the transcription factor Smarrc1 is linked to deregulation of the Wnt/β-catenin signaling pathway and to disease severity in CRC (18). Herein, an enhanced expression of paracrine factors that alter the Wnt/β-catenin signaling pathway was also observed within tumors of Nlrp6-deficient mice.…”
Section: Discussionmentioning
confidence: 99%
“…4 Sox4 was confirmed as an oncogene when transplantation of primary mouse bone marrow cells infected with a Sox4-expressing retroviral vector resulted in myeloid leukemia development in recipient mice. 3 The link between SOX4 and oncogenesis is not limited to leukemias, as it was also found to be overexpressed in human solid tumors, including medulloblastoma, 5 colon, 6 prostate, 7 and lung cancers. 8 However, despite overexpression of SOX4 in these tumors, a tumor-suppressive function for SOX4 has also been suggested in lung and bladder cancer cell lines, 7,9 reflecting a potential cell context-dependent role of SOX4 in tumorigenesis.…”
mentioning
confidence: 99%
“…Increasing evidence has shown that Sox4 is up-regulated in several tumors, such as colon cancer, breast cancer, and salivary gland cancer (23)(24)(25)(26)(27)(28)(29). Although the precise molecular mechanism of Sox4 involvement in tumorigenesis is unclear, several members of the Sox family, including Sox3, Sox7, Sox9, and Sox17 have been shown to inhibit ß-catenin activity (30)(31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…Among Sox family members, Sox4 is of great interest in respect to cancers because recent studies have provided evidence that Sox4 is involved in tumorigenesis of various human cancers (23)(24)(25)(26)(27)(28)(29). To examine the reciprocal relationship between Sox4 and ß-catenin, HEK 293 cells were transfected with expression vectors for FLAG-tagged Sox4.…”
Section: Sox4 Increases the Level Of Endogenous ß-Cateninmentioning
confidence: 99%
See 1 more Smart Citation